Orang-kontrak*: De verbeelding van Javaanse contractarbeiders in Suriname en Deli - Hoefte, Rosemarijn (Acta Neerlandica, 2016)
This article compares the literary representation of Javanese contract laborers in Suriname and Deli (Sumatra). Novels depicting the life of planters and workers, such as Madelon Székely-Lulofs’s Rubber (1931) or Koelie (1932) on Deli, are not part of the Surinamese literary canon. Instead, I use contemporary books and articles, among which publications by missionaries form an important source, and later stories and novels by authors of Surinamese descent, including Bea Vianen, Cynthia McLeod, and Karin Amatmoekrim, in which Javanese history and culture in Suriname are sketched. In contrast to Deli, in Surinamese prose the indentured labor system was only questioned in the postcolonial period.